Method for testing grafting rate of silane grafted polyolefin master batch for photovoltaic packaging
Patent Information
- Application Number
- CN202411738498.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic encapsulation, and in particular relates to a method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation. Background Art
[0002] Photovoltaic power generation will replace traditional energy as an important green energy. Photovoltaic modules, as the core components of power generation units, have shown explosive development, and their core auxiliary materials, packaging films, have also received more and more attention from the industry. With the development of battery technology, based on traditional P-type batteries, N-type batteries represented by tunneling oxide passivation contact (TOPCon), intrinsic thin-film heterojunction (HJT) and interdigitated back contact (IBC) face industrialization needs due to their higher efficiency. The traditional packaging material, thermosetting EVA film, has low water vapor permeability and produces acidic acetic acid after light and heat aging. It can no longer meet the current demand for packaging materials for high-efficiency N-type batteries, so POE film came into being.
[0003] Photovoltaic-grade POE encapsulation film is mainly divided into pure POE and multi-layer composite film of EVA / POE / EVA (EPE) structure. Since POE is a non-polar molecular chain structure, it has poor absorption capacity for additives, which makes it easy for additives to precipitate out of the POE film, causing the film to slip with the glass and battery cells during the production process of the component. The lamination process increases the difficulty of the cross-linking reaction, which ultimately leads to power attenuation of the component due to water vapor intrusion in aging reliability such as HF, PCT, DH, PID, and bubbles on the appearance. More and more manufacturers have begun to carry out front-end modification of POE resins. By grafting silane modification on polyolefin chain segments, such as γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and its oligomers, the prepared POE grafted materials can increase the polarity of POE resin, have better compatibility with other additives, reduce the precipitation of additives to the surface of the film, and avoid the film from slipping during use by the client. The prepared film has long-term storage performance, while ensuring that the components have better aging reliability in HF, PCT, DH, and PID.
[0004] Since there is currently no method in the market to test and characterize the grafting rate of silane-grafted polyolefin masterbatch, it is necessary to provide a test method for the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation, so as to select grafting materials with better compatibility for photovoltaic encapsulation films and reduce the precipitation of additives in the films. Summary of the invention
[0005] The purpose of the present invention is to provide a method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation in view of the existing problems, thereby solving the technical problems existing in the background technology.
[0006] The present invention is achieved through the following technical scheme: A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation, comprising the following steps:
[0007] S1, placing the silane-grafted polyolefin particles into a hot press for tableting and cutting to obtain test samples;
[0008] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0009] S3, placing the test sample in S2 into an ultrasonic oscillator for ultrasonic treatment;
[0010] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying to obtain a pretreated sample;
[0011] S5, placing the pretreated sample in S4 on a fixture of a Fourier transform infrared spectrometer for testing, and testing absorbances A1 and A2;
[0012] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%. The larger the R value, the higher the grafting rate, the better the compatibility with the additive, and the more difficult it is to precipitate.
[0013] Preferably, the polyolefin particles in S1 include one or two of polyolefin resins such as ethylene-octene copolymer particles, ethylene-butene copolymer particles, ethylene-propylene copolymer particles, ethylene-vinyl acetate copolymer, and linear low-density polyethylene.
[0014] Preferably, the pressure of the hot press in S1 is not less than 10 MPa, the double plates are heated, and the heating temperature of the press plates can reach 150 degrees Celsius, preferably 5 MPa and 150 degrees Celsius, to ensure that the polyolefin grafted material is fully melted.
[0015] Preferably, the cutting size of the test sample in S1 is 20 mm in diameter and 5 to 25 um in thickness, preferably 25 um, which can ensure high light transmittance and improve the success rate of tableting.
[0016] Preferably, the ultrasonic time in S3 is 10 to 20 minutes, preferably 10 minutes, to ensure that the additives not involved in the reaction in the polyolefin grafted material are precipitated to the surface, resulting in a larger grafting rate test.
[0017] Preferably, the temperature of the drying box in S4 is 25 degrees Celsius and the humidity is 50%.
[0018] Preferably, the drying time in S4 is 1 to 2 hours to ensure that the ethanol or water in the pretreatment stage is fully volatilized, preferably 1 hour to ensure that the ethanol or water in the pretreatment stage is fully volatilized.
[0019] Preferably, the Fourier transform infrared spectrometer in S5 is tested using a reflection method or a transmission method, and the background resolution of the infrared spectrometer is 4000 cm -1 ~400cm -1 The resolution parameters were used for testing, the scanning times of the infrared spectrometer were 16 or 32 times, and the infrared spectrum compensation included water compensation, carbon dioxide compensation and automatic baseline calibration.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] The invention provides a method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation. The invention can compare the grafting rate data between the same type of auxiliary agents, between different types of auxiliary agents and between different POE particles by quickly measuring the grafting rate of different types of POE grafted materials and silane coupling agent grafted materials. The higher the grafting rate, the better the compatibility of the auxiliary agent and the more difficult it is to precipitate. Therefore, the grafted material with better compatibility can be selected to reduce the precipitation of the auxiliary agent in the film. DETAILED DESCRIPTION
[0022] In order to more clearly understand the technical content of the present invention, the following embodiments are given in detail.
[0023] Embodiment 1
[0024] The present invention provides a technical solution: a method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation, comprising the following steps:
[0025] S1. Press and cut the γ-methacryloxypropyltrimethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0026] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0027] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0028] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0029] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0030] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0031] In this embodiment, the grafting rate test data R1 is in Table 1;
[0032] Embodiment 2
[0033] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0034] S1, putting the γ-methacryloxypropyltrimethoxysilane grafted polyolefin particles prepared from the ethylene-butene copolymer particles into a hot press for tableting and cutting to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0035] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0036] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0037] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0038] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0039] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0040] In this embodiment, the grafting rate test data R2 is in Table 1;
[0041] Embodiment 3
[0042] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0043] S1, putting the γ-methacryloxypropyltrimethoxysilane grafted polyolefin particles prepared from ethylene-propylene copolymer particles into a hot press for tableting and cutting to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0044] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0045] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0046] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0047] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0048] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0049] In this embodiment, the grafting rate test data R3 is shown in Table 1:
[0050] Embodiment 4
[0051] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0052] S1. Press and cut the γ-aminopropyltriethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0053] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0054] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0055] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0056] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0057] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0058] In this embodiment, the grafting rate test data R4 is in Table 1;
[0059] Embodiment 5
[0060] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0061] S1. Press and cut the γ-glycidyloxypropyltrimethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0062] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0063] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0064] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0065] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0066] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0067] In this embodiment, the grafting rate test data R5 is in Table 1;
[0068] Embodiment 6
[0069] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0070] S1. Press and cut the γ-methacryloxypropyltrimethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 10 um;
[0071] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0072] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0073] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0074] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm-1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0075] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0076] In this embodiment, the grafting rate test data R6 is in Table 1;
[0077] Embodiment 7
[0078] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0079] S1. Press and cut the γ-methacryloxypropyltrimethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0080] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0081] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 20 minutes;
[0082] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0083] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0084] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0085] In this embodiment, the grafting rate test data R7 is in Table 1;
[0086] Embodiment 8
[0087] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0088] S1. Press and cut the γ-methacryloxypropyltrimethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0089] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0090] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0091] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 2 hours to obtain a pretreated sample;
[0092] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameter is used for testing, and the reflectance method is used to test the absorbance A1 and A2;
[0093] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0094] In this embodiment, the grafting rate test data R8 is in Table 1;
[0095] Embodiment 9
[0096] A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation comprises the following steps:
[0097] S1. Press and cut the γ-methacryloxypropyltrimethoxysilane grafted polyolefin masterbatch prepared by using ethylene-octene copolymer particles to obtain a test sample with a diameter of 20 mm and a thickness of 25 um;
[0098] S2. Place the test sample in a beaker and add anhydrous ethanol;
[0099] S3, placing the test sample in S2 into an ultrasonic oscillator and performing ultrasonic treatment for 10 minutes;
[0100] S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying for 1 hour to obtain a pretreated sample;
[0101] S5. Place the pretreated sample in S4 on the fixture of the Fourier transform infrared spectrometer for testing. The background resolution of the infrared spectrometer is 4000cm -1 ~400cm -1 The resolution parameters are used for testing, and the absorbance A1 and A2 are tested by the transmission method;
[0102] S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%;
[0103] In this embodiment, the grafting rate test data R9 is in Table 1;
[0104] Infrared reflection method and transmission method are important tools for material structure analysis and qualitative and quantitative analysis. When infrared reflection method is used, when infrared light is irradiated to the sample surface, part of the light is reflected and the other part is absorbed by the sample. By analyzing the intensity and wave number of the reflected light, the infrared spectrum of the sample can be obtained. For solid sample analysis, for solid samples that are opaque or difficult to make into thin films, reflection method is the first choice; when infrared transmission method is used, when infrared light passes through the sample, part of the light is absorbed by the sample and the transmitted light is received by the detector to obtain the infrared spectrum of the sample. For thin film samples, transmission method can obtain a clearer spectrum;
[0105] Table 1
[0106] sample Grafting rate / % Additive compatibility R1 3.53 good R2 2.84 good R3 1.63 generally R4 2.87 good R5 2.97 good R6 3.53 good R7 3.55 good R8 3.54 good R9 2.56 good
[0107] It can be seen from the above embodiments that, by comparing Examples 1, 2, and 3, it can be concluded that the grafting rate of ethylene-octene copolymer particles is higher and the compatibility is better. By comparing Examples 1, 4, and 5, it can be concluded that the grafting rate of γ-methacryloxypropyltrimethoxysilane is higher and the compatibility is better… Using this test method, the grafting rate of different types of POE grafted materials and silane coupling agent grafted materials can be quickly determined, and the grafting rate data between the same type of additives, between different types of additives, and between different POE particles can be compared. The higher the grafting rate, the better the compatibility of the additive, and the more difficult it is to precipitate.
[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation, characterized in that: The following steps are involved: S1, placing the silane-grafted polyolefin particles into a hot press for tableting and cutting to obtain test samples; S2. Place the test sample in a beaker and add anhydrous ethanol; S3, placing the test sample in S2 into an ultrasonic oscillator for ultrasonic treatment; S4, placing the test sample in S3 into a constant temperature and humidity drying oven for drying to obtain a pretreated sample; S5, placing the pretreated sample in S4 on a fixture of a Fourier transform infrared spectrometer for testing, and testing absorbances A1 and A2; S6. Calculation of relative grafting rate (R): R = K (A1 / A2) * 100%.
2. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The polyolefin particles in S1 include one or two of polyolefin resins such as ethylene-octene copolymer particles, ethylene-butene copolymer particles, ethylene-propylene copolymer particles, ethylene-vinyl acetate copolymer, and linear low-density polyethylene.
3. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The pressure of the hot press in S1 is not less than 10 MPa, and double plates are heated.
4. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The cutting size of the test sample in S1 is 20 mm in diameter and 5 to 25 um in thickness.
5. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The sound wave frequency of the ultrasonic oscillator in S3 is 40kHz and the temperature is 25 degrees Celsius.
6. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The ultrasonic time in S3 is 10 to 20 minutes.
7. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The temperature of the drying box in S4 is 25 degrees Celsius and the humidity is 50%.
8. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The drying time in S4 is 1 to 2 hours.
9. The method for testing the grafting rate of silane-grafted polyolefin masterbatch for photovoltaic encapsulation according to claim 1, characterized in that: The Fourier transform infrared spectrometer in S5 uses a reflection method or a transmission method for testing.